Exploring the heat transfer performance of nanofluid as a coolant for power battery pack. Issue 7 (2nd August 2019) - Xu, Xiaoqin; Xiao, Tianli; Chen, Shumei; Lin, Shaoyi
Abstract: Nanofluids with high thermal conductivity coefficient are introduced to the thermal management system of power battery packs for electric vehicles and hybrid electric vehicles. Two typical cooling structures of cylindrical and square battery packs are described, and their flow models are established. By similarity transformations, the nonlinear system of partial differential equations is reduced and then solved numerically by the shooting method. The heat transfer properties of three types of nanofluids, that is, CuO‐EG, Al2 O3 ‐EG, TiO2 ‐EG, are analyzed in detail. It is found that CuO‐EG nanofluid is the best coolant for the cylindrical battery pack, whereas Al2 O3 ‐EG nanofluid is the best choice for square battery pack cooling.